Analisis Sistem Penyediaan Air Minum Malet Kecamatan Susut Kabupaten Bangli Berbasis Aplikasi Epanet 2.2 - I Ketut Soriarta; I Putu Dwikarna Putra (Jurnal Teknik Sipil, 2025)
The availability of water at 3 liters per second (l/s) from the Malet I spring is insufficient to meet the increasing clean water demand of the residents in Tiga Village, which continues to rise year by year. Therefore, the Malet II spring will be utilized to fulfill the clean water needs of Tiga Village. The combined average discharge potential of both springs is approximately 10 l/s. The elevation of the Malet spring is 722 meters above sea level (masl), while the elevation of the Malet Reservoir is 876 masl, resulting in a height difference of 154 meters. Consequently, a pumping system is required to transport water to the Malet Reservoir. Based on the analysis, the clean water demand for the residents of Tiga Village in 2040 is projected to reach 9.9 l/s. Water balance will be achieved between 2042 and 2043. The maximum pressure in the transmission pipes of the Malet Water Supply System is 158.06 meters of water column (mwc) or 15.806 bar. The ideal pipe diameter is 6 inches, producing a flow velocity of 0.57 meters per second (m/s). This flow velocity is within the permissible range of 0.3–2 m/s. The utilization of the Malet II spring provides a viable solution to meet the water needs of Tiga Village residents up to the projected year, 2042.